Analisis Fixed Asset Ratio Pada PT Air Asia Indonesia Tbk. - Dewi Puspita Sari; Aliah Pratiwi (Coopetition : Jurnal Ilmiah Manajemen, 2020)
This study aims to determine the level of fixed asset turnover at PT Air Asia Indonesia Tbk. Asset is still one of several requirements that must be owned by the company in supporting the company's operational activities. The purpose of this study was to determine the Fixed Asset Ratio applied to PT Air Asia Indonesi Tbk. presentation and disclosure of fixed assets in the financial statements. The method used in this research is descriptive method. The research instrument used was financial statement data in the form of a balance sheet. The population used is the company's financial statement data for 19 years from 1999-2018 The sample used in this study is financial data for 5 years (2014-2018) and the sampling used in this study is purposive sampling, data collection techniques used namely literature study. The data analysis technique used is the t one sample. Asset Turnover Results, on average, the turnover of fixed assets at PT Air Asia Indonesia Tbk continues to increase until 2018.